2013
DOI: 10.4236/as.2013.412106
|View full text |Cite
|
Sign up to set email alerts
|

Common beans (<i>Phaseolus vulgaris L.</i>) in the rations for cattle in feedlot

Abstract: To evaluate the inclusion of common beans in the diet of cattle in feedlot on characteristics of productive performance, nutrient digestibility and ruminal fermentation parameters, 15 bulls crossed were used in a completely randomized design. The animals were confined for 64 days, and 21 days of adaptation. We evaluated the inclusion common beans at levels of 0%, 13% and 26%. All diets were isocaloric and isonitrogenous with a 45:55 forage: concentrate ratio. The addition of beans in the diet did not affect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Goes et al (2013) found that the addition of beans in the diet of cattle did not affect animal performance, dry matter intake and feed efficiency. However, the digestibility of dry matter, organic matter, crude protein, ether extract and total carbohydrates decreased with the inclusion of 26 percent of beans.…”
Section: Introductionmentioning
confidence: 91%
“…Goes et al (2013) found that the addition of beans in the diet of cattle did not affect animal performance, dry matter intake and feed efficiency. However, the digestibility of dry matter, organic matter, crude protein, ether extract and total carbohydrates decreased with the inclusion of 26 percent of beans.…”
Section: Introductionmentioning
confidence: 91%